Rapid implementation of teledentistry during the Covid-19 lockdown - Manal Obeid Watfa; Nicole M. Bernfeld; Daniel Oren; Tali Shani; Asaf Zigron; Eyal Sela; Yigal Granot; Amiel A. Dror; Samer Srouji (Elsevier, 2021)
Introduction: The current corona virus disease 2019 (COVID-19) outbreak set new challenges to nearly all health plans and large health organizations worldwide, including movement restrictions, strict limitations in healthcare services, especially in the dental profession, and patient fears regarding potential infection. Telehealth can serve as an effective platform for remote connection between dental healthcare providers and patients, and can help reduce the risk of infection when social distancing is required. Objective: The current study aimed to evaluate the quality of treatment provided via teledentistry, as perceived by patients using the service, as well as their willingness to use online distant medical consultation in the future. Methods: Since March 2020, a new online service was implemented in the Oral Medicine Unit and Oral and Maxillofacial Surgery Department in the Galilee Medical Center, to expand the range of services beyond merely emergency treatments. Results: The current study examined the quality of teledentistry services as perceived by 89 patients participating in at least one teleconsultation, and their acceptance of remote healthcare. Satisfaction rates were high in patients who received both full and partial solution to their chief complaint. Moreover, acceptance of the teledentistry platform was high, even in the older age groups. Conclusions: We propose to implement teledentistry services in current and future pandemics, as well as during routine times, to strengthen our health care system with digital technologies.